Isolation of crude fucoidan from Sargassum wightii using conventional and ultra-sonication extraction methods. (October 2019) - Hanjabam, Mandakini Devi; Kumar, Anuj; Tejpal, C.S.; Krishnamoorthy, Elavarasan; Kishore, Pankaj; Ashok Kumar, K.
Abstract: Fucoidan, a fucose rich sulphated polysaccharide, generally found in cell wall matrix of brown seaweeds possess diverse physiological properties. Crude fucoidan was extracted from Sargassum wightii, a brown seaweed common along the Indian coastline. A comparison was made between hot water extraction (HWE) and ultra-sonication extraction (UAE) methods. The UAE method gave higher yield (14.61 g/100 g) than HWE method (10.59 g/100 g). The UAE fucoidan had lighter colour than HWE, as indicated by Hunter colour values. The water activity values for fucoidans obtained were 0.14 for HWE and 0.19 for UAE. The sulphate content was similar in both fucoidans (̴17%). However, HWE fucoidan had higher content of fucose. The Fourier transform infrared spectroscopy spectra confirmed the presence of sulphate groups in both the fucoidans. The absorption bands at 1245.37 cm −1 and 1294.99 cm −1 in the HWE and UAE fucoidan respectively, indicated the S–O stretching due to sulphate groups in the fucose monomer. The thermal transition temperature as obtained by differential scanning calorimetry for HWE (127.3 °C) was lower than UAE fucoidan (131.8 °C). HWE fucoidan had higher DPPH radical scavenging and reducing power than UAE fucoidan. On the other hand, UAE fucoidan had higher metal chelating activity. The present study demonstrated that ultra-sonication can be an effective alternative for the extraction of sulphated polysaccharide from seaweed, in term of higher yield. The health benefits of Sargassum wightii and fucoidan obtained from it, could be explored by incorporation in different food systems. Graphical abstract: Image 1 Highlights: Crude fucoidan was extracted from Sargassum wightii using hot water extraction (HWE) and ultra-sonication assisted extraction (UAE) methods. The UAE method gave higher yield than HWE method. The sulphate content was similar in both fucoidans. HWE fucoidan had higher content of fucose than UAE fucoidan. HWE fucoidan had higher DPPH radical scavenging and metal chelating activities than UAE fucoidan.